Association between previous history of gout attack and risk of deep vein thrombosis - a nationwide population-based cohort study - Chiu, Chun-Chih (Sci Rep, 2016)
Although the association of hyperuricemia and cardiovascular diseases is well established by previous research studies, the relationship between gout and deep vein thrombosis (DVT) remains unclear. We conducted a nationwide longitudinal cohort study to investigate the relationship between gout and DVT. We used the Taiwan National Health Insurance Research Database to identify patients with gout diagnosed in Taiwan during 2000–2011, and we followed up these patients to determine the incidence of DVT among them. The association between gout and DVT was analyzed by cox proportional hazard model. The study cohort included 35,959 patients with history of gout attack and 35,959 matched controls without gout attack. During the median follow-up of 7.5 ± 3.6 years, the incidence rate of DVT was significantly higher in patients with gout than that in control group (13.48 versus 9.77 per 10(4) person-years, p < 0.001). Kaplan-Meier analysis revealed a tendency toward DVT development in gout patients (log rank test, p < 0.001). In a Cox model, patients with gout were found to have a 1.38-fold (95% confidence interval [CI], 1.18 to 1.62, p < 0.001) higher risk of developing DVT. Hyperuricemia with gout attack could be a possible risk predictor for DVT, but these findings need to be confirmed in future clinical and experimental studies.